Solvent-free Michael addition of 2-cyclohexenone under ultrasonic irradiation in the presence of long chain dicationic ammonium salts - Oge, Aytek; Mavis, Murat Emrah; Yolacan, Cigdem; Aydogan, Feray (Tubitak Scientific & Technological Research Council Turkey, 2012)
Long chain dicationic ammonium salts (1a-1c), easily prepared from tert-amines and dihaloalkanes, were successfully used as efficient phase-transfer catalysts in the Michael addition reaction of various active methylene compounds to 2-cyclohexenone without solvent under ultrasonic irradiation. The investigated dicationic salts were more effective than monocationic tetrabutylammonium bromide, with short reaction times and high yields. This methodology was established under phase-transfer catalytic conditions and ultrasonic effects with many advantages, including the easy and cost-effective synthesis of the catalyst, mild reaction conditions, short reaction times, good yields, simple work-up procedures. and environmental friendliness.
Keywords: Michael addition; phase-transfer catalyst; ultrasound-assisted synthesis; solvent-free reaction; 2-cyclohexenone; CONJUGATE ADDITION; ASYMMETRIC MICHAEL; CATIONIC SURFACTANTS; CHIRAL AMMONIUM; IONIC LIQUIDS; WATER; CONDENSATION; ALDEHYDES; EFFICIENT; Chemistry; Engineering